Differences in expression of gut-homing receptors on CD4+ T cells in black and white HIV-negative men who have sex with men. (15th May 2016) - Kelley, Colleen F.; Lai, Lilin; Ibegbu, Chris; Rosenberg, Eli S.; Kaur, Surinder; Patel, Kalpana; Mulligan, Mark J.; Marconi, Vincent C.; Sullivan, Patrick S.; Amara, Rama R.
Abstract : HIV incidence rates are higher among black men who have sex with men (BMSM) as compared with MSM of other race/ethnicities in the USA. We found that blood memory CD4 + cells from BMSM express higher levels of α4β7, the gut-homing integrin, compared with white MSM. Higher expression of α4β7 on blood CD4 + cells correlated with higher percentage of proliferating CD4 + α4β7 + cells in rectal tissue suggesting increased trafficking of potential HIV target cells to rectal mucosa could increase HIV susceptibility among BMSM.